Позитивний вплив антибіотика тиментину на елімінацію Agrobacterium tumefaciens та регенерацію in vitro пшениці м’якої Triticum aestivum - Горбатюк, І.Р.; Гнатюк, І.С.; Банникова, М.О.; Моргун, Б.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. Effective elimination of bacteria is a crucial factor for efficient plant transformation. Cefotaxime is usually used
to inhibit Agrobacterium cell growth but it inhibits plant regeneration too. So the search continues for a stable nontoxic
for plants antibiotic. Methods. The disc diffusion method was used to show an inhibitory effect of antibiotics Timentin
and Cefotaxime on Agrobacterium tumefaciens strain ABI. 18-day callus of Triticum aestivum cv. Zymoyarka was used
to determine the effect of different antibiotic concentrations on morphogenesis and regeneration. Results. Comparing the
effects of Timentin and Cefotaxime different concentrations on Agrobacterium it was found that Timentin is more efficient –
diameter of inhibitory zone was the same for 350 mg/l Timentin and 500 mg/l Cefotaxime. The optimum concentration of
Timentin (350 mg/l) for the elimination of Agrobacterium did not cause any necrosis but enhanced both the frequency of
morphogenesis and plant regeneration. Conclusions. 350 mg/l Timentin completely eliminates Agrobacterium and increases
both the frequency of regeneration and morphogenesis of bread wheat.
Keywords: Triticum aestivum, in vitro culture, Timentin, Agrobacterium tumefaciens, morphogenesis, regeneration.